SISTEM PENDUKUNG KEPUTUSAN PERKEMBANGAN BELAJAR ANAK TK EL-YAMIEN 1 TUBAN MENGGUNAKAN METODE SMART BERBASIS WEB - Alfi Azqia Uzzulfa Haq; Tanhella Zein Vitadiar; I Kadek Dwi Nuryana; Muhammad Fatkhur Rizal (Inovate, 2024)
El-Yamien 1 Tuban Kindergarten is an Islamic-based kindergarten and is located in Tuban District. Thisresearch focuses on developing a Decision Support System for Assessment of Children's Learning Progressat El-Yamien 1 Tuban Kindergarten using the web-based SMART Method. This research problemaddresses the inefficiency of the existing manual assessment process in schools, which hinders teachers inevaluating children's learning development effectively. The goal was to develop a web-based system thatwould automate the assessment process and provide ratings of children's learning progress. Using theSimple Multi Attribute Rating Technique (SMART) method for decision making, focusing on five criteriafor assessing children's learning progress. The results show that the web-based system simplifies the processof inputting teacher data and automatically produces assessment results, making it easier to evaluatechildren's learning progress. The implications of this research indicate the importance of incorporatingdigital technology in education to improve assessment processes and improve decision making.Keywords: Decision Support System, SMART, Children's Learning Development.